THE PSYCHOLOGICAL ASPECTS OF BEING READY TO DIETARY BEHAVIOR’S CHANGES - Absalyamova, Larysa (PSYCHOLOGICAL JOURNAL, 2018)
The article is dedecated to the problem of the readiness to dietary behavior’s changes. Psychological roots of a person’s readiness to make changes in food behavior are analysed in the article. It is noted that changes in food behavior depend on several factors; among these factors an important place is occupied by individual features of a person. It is underlined that changes of behavioural strategies stands for the principal condition to optimize food behavior of a person. It is underlined that in the process of a forming experiment following features were discovered. In RG1 (research group 1), where correctional work was conducted, all parameters were changed: amount of women with the high and low indexes of restrictive behavior dropped by 8% and 4% respectively, and amount of women with normal values of this parameter increased by 12%. In RG 2 (research group 2), where correctional work was not conducted, all parameters remained at former level. These meaningful differences prove that correctional program helped women to look at themselves and their bodies from an alternative perspective, they became happier with their appearances. The group of women that passed the correctional program is characterized that participants are more happy with their body images, they aspire to change only some personal qualities, keeping other untouched. They are not inclined to be fixed on their personal experience, demonstrating high levels of self-esteem and self-confidence. Their opinion of themselves depends on other’s estimations to a very limited extent, they provide both themselves and other people both high internal freedom and high responsibility. The conclusion is drawn, that we analysed several factors that influence on readiness of a person to make changes in food behavior. Forming experiment confirmed efficiency of correctional psychological help to women with food behavior disorders.